Criterion Validity of the Child's Challenging Behavior Scale, Version 2 (CCBS-2). - Bourke-Taylor, H.; Cordier, Reinie; Pallant, J. (American Occupational Therapy Association, Inc., 2017)
OBJECTIVE: The Child's Challenging Behavior Scale, Version 2 (CCBS-2), measures maternal rating of a child's challenging behaviors that compromise maternal mental health. The CCBS-2, the Child Behavior Checklist (CBCL), and the Strengths and Difficulties Questionnaire (SDQ) were compared in a sample of typically developing young Australian children. METHOD: Criterion validity was investigated by correlating the CCBS-2 with "gold standard" measures (CBCL and SDQ subscales). Data were collected in a cross-sectional survey of mothers (N = 336) of children ages 3-9 yr. RESULTS: Correlations with the CBCL externalizing subscales demonstrated moderate (? = .46) to strong (? = .66) correlations. Correlations with the SDQ externalizing behaviors subscales were moderate (? = .35) to strong (? = .60). CONCLUSION: The criterion validity established in this study strengthens the psychometric properties that support ongoing development of the CCBS-2 as an efficient tool that may identify children in need of further evaluation.